A prospective study of trends in consumption of cigarettes and alcohol among adults in a rural Ugandan population cohort, 1994–2011. Issue 4 (14th January 2015) - Asiki, Gershim; Baisley, Kathy; Kamali, Anatoli; Kaleebu, Pontiano; Seeley, Janet; Newton, Robert
Abstract Objectives To characterise trends over time in smoking and alcohol consumption in a rural Ugandan population between 1994 and 2011. Methods We used self‐reported data from a long‐standing population cohort – the General Population Cohort. From 1989 to 1999, the study population comprised about 10 000 residents of 15 adjacent villages. From 1999, 10 more villages were added, doubling the population. Among adults (≥13 years, who comprise about half of the total study population), data on smoking were collected in 1994/1995, 2008/2009 and in 2010/2011. Data on alcohol were collected in 1996/1997, 2000/2001, 2009/2010 and 2010/2011. Results The reported prevalence of smoking among men was 17% in 1994/1995, 14% in 2008/2009 and 16% in 2010/2011; equivalent figures for women were 1.5%, 1% and 2%. In the most recent time period, for both sexes combined, prevalence of smoking increased from 1.5% in those aged <29 years, to 18% in those 50+ years (P < 0.001); prevalence was 14.8% in the lowest tertile of socio‐economic status, decreasing to 3.7% in the highest (P < 0.001). For alcohol consumption, current drinking was reported by 39% in 1996/1997, 35% in 2000/2001 and 28% in 2010/2011; men were more likely to drink than women (32.9% vs. 23.5% in 2010/2011) and consumption increased with age (P < 0.001); and was associated with low socio‐economic status, riskier sexual behaviour and being HIV positive (P < 0.001). Conclusions In this rural Ugandan population, consumption of cigarettes and alcohol is higher among men than women, increases with age and is more frequent among those with low socio‐economic status. We find no evidence of increases in either exposure over time.